Contribution to Studies of Medieval Galician-Portuguese Lyric in Argentina in the 1960s: the Work of Nydia G. B. de Fernández Pereiro - Disalvo, Santiago; Nusch, Carlos (Madrygal. Revista de Estudios Gallegos, 2018)
The contribution by many Argentines to the Iberian medieval studies during the 20th century is a widely known and documented fact. The same can be said of the Brazilian and Argentine contributions to the specific research field of Galician-Portuguese lyric. It is necessary, at this point of history, to revisit and review these publications of diverse magnitude and perspective, such as the academic writings of Nydia G. B. de Fernández Pereiro, in order to evaluate and consider its later impact and legacy. This paper comes forth as one of the first results in the investigation by some members of the project “Tensions and contacts in Romanic lyric tradition from the Middle Ages and Renaissance towards its projections in Modernity” (Dir. G. Chicote and S. Disalvo, 2014-2017), in the IdIHCS and the Facultad de Humanidades y Ciencias de las Educación (UNLP, Argentina).
Keywords: Galician-Portuguese Lyric; Troubadour lyric; Nydia G. B. de Fernández Pereiro; Medieval Studies; Argentina.